Thymic T Cell Lymphosarcoma in an Akkaraman Sheep - İncili, Canan Akdeniz; Eroksuz, Yesari; Abayli, Hasan; Eröksüz, Hatice (My University, 2024)
Thymic T-cell lymphosarcoma is a rare malignancy that arises from the thymus and can spread to other organs in animals. We report a case of thymic lymphosarcoma in an 11-month-old Akkaraman sheep. The occurrence of thymic lymphosarcoma in sheep and other animals without bovine leukemia virus (BLV) infection is still poorly understood. PCR analysis showed that the tumor was unrelated to BLV. In conclusion, our findings indicate that the sheep had thymic T-cell lymphosarcoma without BLV infection. Further research is needed to understand the etiology and pathogenesis of thymic lymphosarcoma in sheep and other animals.
Keywords: Sheep; Pathology; thymic lymphoma